Incidence, features, and outcomes of cytomegalovirus DNAemia in unmanipulated haploidentical allogeneic hematopoietic stem cell transplantation with post‐transplantation cyclophosphamide. Issue 1 (15th November 2019) - Huntley, Dixie; Giménez, Estela; Pascual, María Jesús; Hernández‐Boluda, Juan Carlos; Gago, Beatriz; Vázquez, Lourdes; Piñana, José Luis; García, Magdalena; Pérez, Ariadna; Serrano, David; Hernández, Marta; Albert, Eliseo; et al.
Abstract: Background: Conflicting data have been published as to the risk of cytomegalovirus (CMV) DNAemia and CMV disease in patients undergoing haploidentical hematopoietic stem cell transplantation (haplo‐HSCT) with post‐transplantation cyclophosphamide. Methods: We conducted a multicenter retrospective study including 118 patients subjected to unmanipulated haplo‐HSCT to further clarify this issue. An historic cohort comprising 165 patients undergoing other transplant modalities (HLA‐matched related, matched unrelated or mismatched) was built for comparison purposes. Plasma CMV DNA monitoring was performed using two highly sensitive real‐time PCR assays. Results: Overall, the cumulative incidence of CMV DNAemia, recurrent CMV DNAemia, and CMV DNAemia requiring preemptive antiviral therapy in patients undergoing haplo‐HSCT was 63.9%, 34.9%, and 50.1%, respectively. These figures were rather comparable for other transplant modalities ( P = .22, P = .13 and P = .72, respectively). A trend toward longer duration of episodes and shorter CMV DNA doubling times was observed in haplo‐HSCT patients in comparison with other transplant modalities. Furthermore, median CMV DNA peak load was significantly higher in haplo‐HSCTs ( P = .008), yet overall mortality by day 180 and 365 was the same across comparison groups. There were five cases of CMV disease, and all occurred in haplo‐HSCT patients. This latter observation is worrying and merits further investigation. Conclusions: The incidence of initial and recurrent episodes of CMV DNAemia either requiring or not antiviral therapy in unmanipulated haplo‐HSCT was comparable to other transplant modalities in our cohort.